Seven-octave ultra-bright pulse generation - Enders, Michael T.; Elu, Ugaitz; Maidment, Luke; Vamos, Lenard; Tani, Francesco; Novoa, David; Frosz, Michael H.; Badikov, Valeriy; Badikov, Dimitrii; Petrov, Valentin; Russell, Philip St. John; Biegert, Jens (Optics InfoBase Conference Papers, 2021)
We present an ultra-bright carrier-envelope-phase-stable light source spanning seven octaves (340 nm to 40 000 nm) simultaneously by combining soliton self-compression, dispersive wave generation, and intra-pulse difference frequency generation in a newly-developed nonlinear crystal.
CRIS-Team Scopus Importer:2021-12-03